2010
DOI: 10.4025/actasciagron.v32i1.900
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização fenotípica de rizóbio nativos isolados de solos da Amazônia e eficiência simbiótica em feijão caupi

Abstract: RESUMO.A tlxaçâo biológica do nitrogênio é de fundamental importancia na sustciuabilidadc agrícola, c a caraeterizaçao fenotipica rizobiat cniuribui para o conhccimciuo da siia diversidade cm coleçoes c para a luilizaçâo posterior cm sistemas agrícolas. O objetivo deste trabalho foi avaliar a diversidade fenotipica dc rizóbio isolados dc solos da Amazonia e suas eficiencias simbióticas quando inoculados cm tcijáo caupi {V'i^na iwiiuiaéhita L. Walp.). Os isolados nativos apresentaram diversidade quanto as carac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
1
Order By: Relevance
“…Chagas Junior et al (2010) found that the cultivar BRS Pujante nodulated abundantly with all evaluated strains, with lower nodulation rates observed in the nitrogen fertilization and in the absolute control treatments.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Chagas Junior et al (2010) found that the cultivar BRS Pujante nodulated abundantly with all evaluated strains, with lower nodulation rates observed in the nitrogen fertilization and in the absolute control treatments.…”
Section: Resultsmentioning
confidence: 93%
“…Among the newly developed cultivars, only the "Mulato" type, BRS Pujante, had its responses to inoculation studied and has been proven to be highly responsive to the practice (Chagas Junior et al, 2010). The "Canapu" type, 'BRS Acauã'; the "Fradinho" type, 'BRS Carijó'; and the black-coated 'BRS Tapaihum' have short cycle and high levels of minerals and micronutrients in grains (Santos et al, 2008;Santos, 2011); but, in spite of their favorable technological features, the efficiency of their association with rhizobia is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The SE of each rhizobia isolate and the recommended strains was calculated according to the formula SE = (total N fixed−total N without N)/(total N for C+N−total N for C−N) × 100 (Chagas‐Junior et al . ), where SE = symbiotic efficiency; total N fixed = nitrogen accumulation of inoculated treatment; total N for C+N = nitrogen accumulation of the treatment with the application of N; total N for C–N = nitrogen accumulation of the treatment with no N application.…”
Section: Methodsmentioning
confidence: 99%
“…O N é um dos nutrientes mais limitantes à produção de cereais nas regiões de clima tropical, e sua fixação biológica (FBN) é importante para a produção e sustentabilidade dos sistemas agrícolas (CHAGAS JÚNIOR; OLIVEIRA; NASCIMENTO DE OLIVEIRA, 2015). Um dos exemplos mais bemsucedidos de FBN é o caso da soja no Brasil, onde a utilização de inoculantes com Bradyrhizobium proporcionou uma economia anual de US$ 7 bilhões, em fertilizantes nitrogenados.…”
Section: Introductionunclassified